Governing Boards in Postsecondary Education - Dennison, John. D.; Harris, Robert (Canadian Journal of Higher Education, 1984)
Since 1960 postsecondary education in Canada has been characterized by the development of a large number of non-university institutions, usually called colleges or technical institutes. Provincial government policy has been to delegate policy and management roles in these institutions to governing boards, composed largely of lay appointees. This study examines the views held by board members in one province, British Columbia, towards many of the most important issues in curriculum, management, and structure which affect the non-university sector. The results indicate that board members tend to reject strong centralization of the system. Further, they support the essential values which have characterized British Columbia colleges as comprehensive, accessible, community-based institutions governed by lay boards.